Real-time optimization for smart automation of surface irrigation - Smith, Rod, author; Gillies, Malcolm, author; Koech, Richard, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
A system for the real-time optimization of furrow irrigation is described. The system estimates the soil infiltration characteristics in real-time and utilizes the data to control the same irrigation event to give optimum performance for the current soil conditions. The main features of the system are: the use of a model infiltration curve and a scaling process to describe the current soil infiltration characteristic; measurement of the inflow rate to the furrows; measurement of the water advance at a point approximately midway down the furrow; and a microcomputer running a hydraulic simulation program based on the full hydrodynamic model to predict the optimum time to cut-off. The system was trialed on a furrow-irrigated commercial cotton property utilizing pipes through the bank (PTBs) to supply groups of furrows. The initial observations from these trials are presented in this paper and demonstrate that improvements in water use efficiency are potentially achievable through the use of the system. Extensions to the system to improve its performance and to make it applicable to bay irrigation are described.
Irrigated agriculture responds to water use challenges
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.